2014
DOI: 10.1038/ajg.2013.423
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Burden of Constipation in the United States: An Analysis of National Trends in the United States from 1997 to 2010

Abstract: The number of inpatient discharges for constipation and associated costs has significantly increased between 1997 and 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…20 In the United States, the direct expenditure per-patient for constipation which includes medications, hospitalizations, out-patient services, emergency visits, and laboratory tests ranged from $1912 to $7522 per year 19 and increased several-fold between 1997 and 2010. 22 Moreover, a study revealed that up to 50% of chronic constipation and IBS patients use alternative or non-prescription medications, especially by women and patients with higher education. 19 Hence, subtype differentiation, especially identifying dyssynergic defecation, and providing a specific treatment such as biofeedback therapy, can minimize laxative usage and optimize health care utility.…”
Section: Introductionmentioning
confidence: 99%
“…20 In the United States, the direct expenditure per-patient for constipation which includes medications, hospitalizations, out-patient services, emergency visits, and laboratory tests ranged from $1912 to $7522 per year 19 and increased several-fold between 1997 and 2010. 22 Moreover, a study revealed that up to 50% of chronic constipation and IBS patients use alternative or non-prescription medications, especially by women and patients with higher education. 19 Hence, subtype differentiation, especially identifying dyssynergic defecation, and providing a specific treatment such as biofeedback therapy, can minimize laxative usage and optimize health care utility.…”
Section: Introductionmentioning
confidence: 99%
“…Th is number is substantially higher than the $850 million dollars spent on inpatient visits for constipation in 2010 ( 15 ). Th e significant economic burden of constipation-related ED visits, even in comparison with the cost of constipation in the inpatient setting, is the result of the increasing number of ED visits and rising costs of the individual ED visits.…”
Section: Discussionmentioning
confidence: 97%
“…Although patients with CC are typically treated as outpatients, a recent study found that 48,450 patients were discharged from the US hospitals with a primary diagnosis of constipation and aggregate annual costs in excess of $850 million (adjusted for infl ation) in 2010 ( 15 ). Th ese discharges and associated costs signifi cantly increased from 1997, with a 353% increase in aggregate costs and a 129% increase in discharges from 1997 to 2010 ( 15 ). However, the inpatient population with CC only accounts for a small fraction of patients with constipation; it is more likely for patients with CC to visit the emergency department (ED) for treatment without admission to the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In a systematic review that reported the prevalence of chronic idiopathic constipation in 41 separate study populations (including 261 040 subjects), the pooled prevalence of chronic idiopathic constipation in all studies was 14% (95% CI, 12-17%), with lower prevalence in southeast Asian studies. 3 In a population-based study conducted in Olmsted County, Minnesota, the cumulative incidence of chronic constipation over a 15-year period (1988 to 2003) was 17.4%.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the current analysis, we focused exclusively on patients with slow colonic transit in order to clarify whether the regional colonic transit pattern is useful in identifying evacuation disorders in constipated patients, since there is limited information about regional colonic transit between those patients with slow colonic transit compared to those without evacuation disorders. In this study, we aimed to evaluate: (1) clinical features and anorectal function, (2) differences in regional colonic transit according to the presence or absence of evacuation disorders, and (3) association of colonic transit with gender in patients with objectively slow colonic transit.…”
Section: Introductionmentioning
confidence: 99%